Impact of the Malnutrition on Mortality in Elderly Patients Undergoing Percutaneous Coronary Intervention - Chen L (Dove Medical Press, 2021)
Liling Chen,1,* Zhidong Huang,2,* Jin Lu,1,* Yanfang Yang,1 Yuxiong Pan,1 Kunming Bao,1 Junjie Wang,1 Weihua Chen,1 Jin Liu,2 Yong Liu,2 Kaihong Chen,1 Weiguo Li,1 Shiqun Chen2 1Department of Cardiology, Longyan First Affiliated Hospital of Fujian Medical University, Longyan, 364000, People’s Republic of China; 2Department of Cardiology, Guangdong Provincial Key Laboratory of Coronary Heart Disease Prevention, Guangdong Cardiovascular Institute, Guangdong Provincial People’s Hospital, Guangdong Academy of Medical Sciences, Guangzhou, 510080, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shiqun ChenDepartment of Cardiology, Guangdong Provincial Key Laboratory of Coronary Heart Disease Prevention, Guangdong Cardiovascular Institute, Guangdong Provincial People’s Hospital, Guangdong Academy of Medical Sciences, Guangzhou, 510080, People’s Republic of ChinaTel +86 2083827812 ext. 10528Fax +86 2083851483Email shiqunchen@126.comWeiguo LiDepartment of Cardiology, Longyan First Affiliated Hospital of Fujian Medical University, Longyan, 364000, People’s Republic of ChinaTel +86 5973082105Fax +86 5972100500Email lwg701201@163.comPurpose: Malnutrition has been shown to be related to adverse clinical outcomes in patients with heart failure, hypertension, atrial fibrillation and other cardiovascular diseases. However, in the patients with coronary artery disease (CAD) undergoing percutaneous coronary interventions (PCI), especially in the elderly, the association of nutritional state and all-cause mortality remains unknown. We aimed to investigate the association of malnutrition with all-cause mortality in the elder patients undergoing PCI.Patients and Methods: Based on the largest retrospective and observational cohort study from January 2007 to December 2017, the Controlling Nutritional Status (CONUT) score was applied to 21,479 consecutive patients with age ≥ 60 who undergoing PCI for nutritional assessment. Participants were classified as absent, mild, moderate and severe malnutrition by CONUT score. The Kaplan–Meier method was used to compare all-cause mortality among the above four groups. Multivariable Cox proportional hazard regression analyses were performed to examine the association of malnutrition with all-cause mortality.Results: According to the CONUT score, 48.19%, 15.08% and 0.94% patients were mildly, moderately and severely malnourished, respectively. During a median follow-up of 5.16 years (interquartile range: 3.02 to 7.89 years), 3173 (14.77%) patients died. Kaplan–Meier analysis showed that the risk of all-cause mortality was significantly higher in patients with a worse nutritional status. Compared with normal nutritional state, malnutrition was associated with significantly increased risk for all-cause mortality (adjusted hazard ratio for mild, moderate and severe degrees of malnutrition, respectively: 1.20 [95% confidence interval (CI): 1.09 to 1.33], 1.32 [95% CI: 1.17 to 1.49] and 1.76 [95% CI: 1.33 to 2.33]).Conclusion: Malnutrition is prevalent among elderly patients with CAD undergoing PCI, and is strongly related to the all-cause mortality increasing. For elderly patients with CAD undergoing PCI, it is necessary to assess the status of nutrition, and evaluate the efficacy of nutritional interventions.Keywords: malnutrition, elderly, percutaneous coronary intervention, Controlling Nutritional Status score